Analysis of mechanisms regulating expression of the ver-1 gene, involved in aflatoxin biosynthesis. - Liang, S H (1997)
Previous studies have shown that ver-1A encodes an enzyme which is directly involved in the conversion of versicolorin A to demethylsterigmatocystin during aflatoxin B1 (AFB1) biosynthesis in the filamentous fungus Aspergillus parasiticus. In this study, two different tools were utilized to study the regulation of ver-1A expression at the level of transcription and protein accumulation. First, a ver-1A cDNA was expressed in Escherichia coli with the vector pMAL-c2. The resulting maltose-binding protein-Ver-1A fusion protein was purified and used to generate polyclonal antibodies. Western blot analyses showed that these antibodies specifically recognized the Ver-1 protein (approximately 28 kDa) in cell extracts of Aspergillus parasiticus SU1. Second, a GUS (uidA; encodes beta-glucuronidase) reporter system was developed by fusing the ver-1A promoter and transcription terminator to the GUS gene. Reporter constructs were transformed into A. parasiticus, resulting in a single copy of the ver-1A-GUS reporter integrated adjacent to the wild-type ver-1A gene (3' end) in the chromosome. Western blot analysis, Northern hybridization analysis, and a GUS activity assay were used to analyze transformants. The timing of appearance and pattern of accumulation of GUS transcript and GUS protein in transformants were consistent with the timing of appearance and pattern of accumulation of ver-1 transcript and Ver-1 protein. These data suggested that the GUS gene was under the same regulatory control as the wild-type ver-1 gene and confirmed that transcriptional regulation plays an important role in ver-1A expression. Integration of the ver-1A-GUS reporter construct at the niaD locus resulted in 500-fold-lower GUS activity, but the temporal pattern of accumulation of GUS activity was not affected. Therefore, chromosomal location can play a role in determining the level of gene expression in A. parasiticus and should be an important consideration when analyzing promoter function in this organism.